The human papillomavirus E7-E2 interaction mechanism in vitro reveals a finely tuned system for modulating available E7 and E2 proteins - Smal, Clara (2009)
Transcription of the human papillomavirus E7 oncoprotein is negatively controlled by the viral E2 protein, and loss of this repression leads to irreversible transformation and carcinogenesis. Here we show that interaction of the HPV16 E7 protein with the DNA binding domain of the E2 protein (E2C) leads to ionic strength-dependent hetero-oligomerization even at the lowest concentrations measurable. Titration experiments followed by light scattering and native gel electrophoresis show insoluble oligomeric complexes with a >or=2000 nm diameter and intermediate soluble complexes 40 and 115 nm in diameter, respectively, formed in excess of E2C. A discrete oligomeric soluble complex formed in excess of E7 displays a diameter of 12 nm. The N-terminal domain of E7 interacts with E2C with a K(D) of 0.1 muM, where the stretch of residues 25-40 of E7, encompassing both a PEST motif and phosphorylation sites, is sufficient for the interaction. Displacement of the soluble E7-E2C complex by an E2 site DNA duplex and site-directed mutagenesis indicate that the protein-protein interface involves the DNA binding helix of E2. The formation of complexes of different sizes and properties in excess of either of the viral proteins reveals a finely tuned mechanism that could regulate the intracellular levels of both proteins as infection and transformation progress. Sequestering E2 into E7-E2 oligomers provides a possible additional route to uncontrolled E7 expression, in addition and prior to the disruption of the E2 gene during viral integration into the host genome